Sugar, Steam and Steel: The Industrial Project in Colonial Java, 1830-1850 - Roger Knight, G. (University of Adelaide Press, 2014)
Sugar, Steam and Steel is about cane sugar and the transformation of an Indonesian island into the â Oriental Cubaâ during the middle decades of the nineteenth century. Between the 1830s and the 1880s, sweetener manufacture in Dutch-controlled Java â the crown jewel of the erstwhile Netherlands Indies â drew decisively away in matters of technology and sugar science from other Asian centres of production which had once equaled or, more often, surpassed it in terms of both output and know-how. Along with its larger and altogether more famous Caribbean counterpart, Javaâ s industry came to occupy a position at the apex of the trade in what had become by this date a key global commodity.